2013
DOI: 10.1001/jamapsychiatry.2013.44
|View full text |Cite
|
Sign up to set email alerts
|

Altered Reward Processing in Adolescents With Prenatal Exposure to Maternal Cigarette Smoking

Abstract: ; for the IMAGEN Consortium IMPORTANCE Higher rates of substance use and dependence have been observed in the offspring of mothers who smoked during pregnancy. Animal studies indicate that prenatal exposure to nicotine alters the development of brain areas related to reward processing, which might be a risk factor for substance use and addiction later in life. However, no study has examined the effect of maternal smoking on the offspring's brain response during reward processing. OBJECTIVE To determine whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 60 publications
4
38
0
Order By: Relevance
“…Ideally, the field needs prospective studies that include the developmental window allowing assessment of the initiation of alcohol use and development of alcohol dependence. Relevant to this need, findings from the large, multisite IMAGEN consortium have contributed importantly to our understanding of the role of reward circuitry in young people at risk for addiction or early in the process of substance use (e.g., [50], [51], [52]). This study has reported that adolescents who are smokers [50], had prenatal exposure to nicotine [51], or had “potentially problematic” substance use [52] exhibit low VS responsiveness to reward.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ideally, the field needs prospective studies that include the developmental window allowing assessment of the initiation of alcohol use and development of alcohol dependence. Relevant to this need, findings from the large, multisite IMAGEN consortium have contributed importantly to our understanding of the role of reward circuitry in young people at risk for addiction or early in the process of substance use (e.g., [50], [51], [52]). This study has reported that adolescents who are smokers [50], had prenatal exposure to nicotine [51], or had “potentially problematic” substance use [52] exhibit low VS responsiveness to reward.…”
Section: Discussionmentioning
confidence: 99%
“…Relevant to this need, findings from the large, multisite IMAGEN consortium have contributed importantly to our understanding of the role of reward circuitry in young people at risk for addiction or early in the process of substance use (e.g., [50], [51], [52]). This study has reported that adolescents who are smokers [50], had prenatal exposure to nicotine [51], or had “potentially problematic” substance use [52] exhibit low VS responsiveness to reward. Similarly, although we were not able to examine brain function before and after onset of alcohol use or dependence, we note that our sample has unique features that allow us to investigate frontostriatal function early in the course of alcohol use problems.…”
Section: Discussionmentioning
confidence: 99%
“…Namely, relative to nonsmokers, smokers display blunted subjective, behavioral, and neurobiological responses to nondrug rewards (e.g., al-Adawi & Powell, 1997; Martin-Soelch, Missimer, Leenders, & Schultz, 2003; Rose et al, 2012). These biases may be related to neuroadaptations associated with chronic cigarette use, preexisting vulnerabilities in reward functioning, or both (George & Koob, 2010; Kalivas & Volkow, 2005; Muller et al, 2013; Nees et al, 2013; Schneider et al, 2012; Sweitzer, Donny, & Hariri, 2012). Regardless of origin, this relative insensitivity to nondrug rewards presumably diminishes the impact of potential sources of motivation for maintaining smoking abstinence and thus serves as an important obstacle to smoking cessation.…”
Section: Introductionmentioning
confidence: 99%
“…5 Nonetheless, children with ADHD born from mothers who smoked during pregnancy have been reported to have more severe behavioural problems than children with ADHD born from nonsmoking mothers, with a dose-response relationship between the amount smoked and several cognitive and clinical variables in the children. 6 At a neurobiological level maternal smoking during pregnancy has been shown to be associated with grey matter loss and cortical thinning 7 as well as functional alteration in neural circuitry involved in inhibitory control and reward 8,9 in children. There is also strong epidemiological evidence that smoking is associated with increased risk for dementia and the development of Alzheimer disease.…”
Section: Smoking As a Causal Factor For Psychiatric Disordersmentioning
confidence: 99%